A COMPARATIVE STUDY OF MENTAL SKILLS ON NATIONAL LEVEL MALE AND FEMALE BOXERS (International Journal of Food and Nutritional Sciences, 2023)
The main purpose of this research was to compare mental skills of male and femaleBoxers by Ottawa (OMSAT-3) Questionnaire. The research study was a descriptiveappliedone. The data collection instrument was a questionnaire based on Ottawaquestionnaire that measured some mental skills factors. The subject was 50 male and50 female National Level Boxing players. T independent test was applied in order toanalyze the related data to compare the results at p 0.05 level. The results indicatedthat the rate of Confidence, Relaxation, Imagery skills is higher in male Boxers incompare to female. However, the rate of Stress Control, Focusing and CompetitionPlanning skills is higher in Female Boxers as compared to Male Players